A complex pattern of post‐divergence expansion, contraction, introgression, and asynchronous responses to Pleistocene climate changes in two Dipelta sister species from western China. Issue 3 (20th August 2019) - Tian, Bin; Fu, Yi; Milne, Richard I.; Mao, Kang‐Shan; Sun, Yong‐Shuai; Ma, Xiang‐Guang; Sun, Hang
Abstract: The well‐known vicariance and dispersal models dominate in understanding the allopatric pattern for related species and presume the simultaneous occurrence of speciation and biogeographic events. However, the formation of allopatry could postdate the species divergence. We examined this hypothesis using DNA sequence data from three chloroplast fragments and five nuclear loci of Dipelta floribunda Maxim. and D. yunnanensis Franch, two shrub species with the circum Sichuan Basin distribution, combining the climatic niche modeling approach. The best‐fit model supported by the approximate Bayesian computation analysis indicated that D. floribunda and D. yunnanensis diverged during the mid‐Pleistocene period, consistent with the largest glacial period in the Qinghai–Tibet Plateau. The historically interspecific gene flow was identified, but seemed to have ceased after the last interglacial period, when the range of D. floribunda moved northward from the south of the Sichuan Basin. Furthermore, populations of D. floribunda had expanded obviously in the north of the Sichuan Basin after the last glacial maximum (LGM). Relatively, the range of D. yunnanensis expanded before the LGM, and reduced during the post‐LGM especially in the north of the Sichuan Basin, reflecting the asynchronous responses of related species to contemporary climate changes. Our results suggested that complex topography should be considered in understanding distributional patterns, even for closely related species and their demographic responses.